STUDI KOMPETENSI KEMAMPUAN MENULIS DI KALANGAN MAHASISWA - Dhimas Asih Kusuma Persadha (MUADDIB Jurnal Kependidikan dan Keislaman, 2016)
This research aimed to know the student’s skill in writing scientific-papers, by reviewing to some aspects (1) the ability in developing scientific-papers content, (2) the ability in organizing the scientific-papers, (3) the ability in using scientific-papers terms and vocabularies, (4) The ability in using scientific languages in scientific-papers and (5) the ability to apply an orthography and writing techniques in scientific-papers. This research used descriptive methods. The result of this research showed that (1) the student’s scientific-papers writing abilities reviewed from how they develop scientific papers content was considered sufficient. (2) The student’s scientific-papers writing abilities reviewed through how they organize scientific-paper was sufficient. (3) The student’s scientific-papers writing abilities reviewed through their ability in using scientific-papers terms and vocabularies was sufficient. (4) The student’s scientific-papers writing abilities review through the aspect of using scientific languages was sufficient. (5) The student’s scientific-papers writing abilities review through apply an orthography and writing techniques scientific-papers was also sufficient.